Old drugs for new uses: pharmacokinetic assessment to support Oxfendazole repurposing as a flukicidal compound - Ceballos, Laura (2018)
Introduction: Fascioliasis caused by Fasciola hepatica can cause considerable financial losses in livestock production. The main strategy for liver fluke control is based on the use of chemical-based treatments. However, the frequent use of effective flukicidal compounds had led to the development of drug resistance, largely to triclabendazole, the most extensively used drug.   Oxfendazole (OFZ) is a broad spectrum anthelmintic used as nematodicidal, without flukicidal activity at therapeutic doses (5 mg/kg). However, activity against F. hepatica has been reported after a single OFZ dose of 30 mg/kg in both sheep and pigs. The goals of the current work were 1) to compare the plasma pharmacokinetic (PK) profile of different OFZ doses in non-infected sheep, and 2) to evaluate the dose-related pattern of in vivo accumulation of OFZ/metabolites into adult F. hepatica. Materials and methods: 1) PK trial: sheep were allocated into two groups (n=6 each) and orally treated with OFZ at either 5 (OFZ5) or 30 (OFZ30) mg/kg. Blood samples were collected during 96 h post-treatment, and plasma analyzed for OFZ/metabolites by HPLC. 2) Drug accumulation trial: Animals (8) were each orally infected with seventy five (75) metacercariae of F. hepatica. Sixteen weeks after infection, animals were randomly allocated into two experimental groups (n=4) and orally treated with OFZ at either 5 or 30mg/kg. Animals were killed at different times post-treatment and samples of blood, bile, liver and adult liver flukes were obtained. Samples were analyzed by HPLC. Results and conclusions: OFZ parent drug was the main analyte detected in plasma from OFZ treated sheep. The Cmax and AUC0-t values were approx. 4-fold higher in the OFZ30 group (2.5±0.6 µg/mL and 83.7 ± 20.5 µg.h/mL, respectively), compared to that observed after the 5 mg/kg dose (0.6±0.1 µg/mL and 18.0±3.7 µg.h/mL, respectively). These differences were also reflected in the pattern of OFZ accumulation into F. hepatica, which results 332 % higher after the 30 mg/kg dose (4.28 µg/g) compared to the lower dose (0.99 µg/g). The data shown here demonstrates that the OFZ dose increment is associated with a higher plasma drug exposure and accumulation into the target parasite, which help to explain OFZ efficacy against adult liver flukes at 30 mg/kg dose. The reported pharmacological data may contribute to assess OFZ repurposing for a new use as flukicidal.